Mass Transfer in a Closed-cycle Solid-liquid Extraction Unit - Ali, Asbi (Universiti Putra Malaysia Press, 1994)
Solid-liquid extraction is a very important process in the sugar industry, in which sucrose from sugar beets is leached by utilizing hot water as a solvent. In this simulation study, solid-to-fluid mass transfer coefficients were determined by measuring extraction rates of sugar in a closed-cycle extractor. Measurements were made for four flow rates: 3.0, 3.5, 4.0 and 4.5 ml/s over a temperature range of 45 - 65°C at atmospheric pressure. The effects of temperature and solvent velocity on mass transfer coefficients were found to be positive, and the calculated activation energies for the extraction process were found to be in the range of4.0 to 5.4 kJ/kmol K